1966
DOI: 10.1111/j.1939-0025.1966.tb02393.x
|View full text |Cite
|
Sign up to set email alerts
|

Life history differences in identical twins discordant for schizophrenia.

Abstract: Eleven pairs of identical twins, in which one had been previously hospitalized for schizophrenia or borderline schizophrenia, have been intensively studied, along with their parents, at the National Institutes of Health. A number of interacting features tend to consistently differentiate the life course of the index from the control twins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

1966
1966
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(21 citation statements)
references
References 15 publications
0
20
0
1
Order By: Relevance
“…On the basis of their test performance alone they are frequently indistinguishable from patients with organic brain damage (Golden ef af., Watson, 1971). Furthermore, a number of studies have reported the presence of motor disorders and other features suggestive of neurological dysfunction in unselected groups of psychiatric patients and particularly those with severe and chronic forms of schizophrenia (Rogers, 1985;Pollin et al, 1966;Rochford et af., 1970).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of their test performance alone they are frequently indistinguishable from patients with organic brain damage (Golden ef af., Watson, 1971). Furthermore, a number of studies have reported the presence of motor disorders and other features suggestive of neurological dysfunction in unselected groups of psychiatric patients and particularly those with severe and chronic forms of schizophrenia (Rogers, 1985;Pollin et al, 1966;Rochford et af., 1970).…”
Section: Introductionmentioning
confidence: 99%
“…Highly intensive examinations of MZ twins discordantly affected with schizophre nia have been the focus of a project carried out by Pollin et al [1966], also at the Na tional Institute of Mental Health. Eleven pairs of MZ twins in which 1 twin had pre viously been hospitalized for schizophrenia or borderline schizophrenia were carefully investigated along with their parents.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Maternal TH excess during pregnancy results in an increased incidence of pre-eclampsia and low birth weight, the latter being due to premature delivery (Millar et al 1994), but little is known regarding its effects on neurodevelopment. Two early studies independently reported a high incidence of hyperthyroidism in mothers of schizophrenics (Pollin et al 1966, MacSweeney et al 1978; however, these findings remain to be confirmed.…”
Section: Introductionmentioning
confidence: 92%